"Permission to Touch": Nurses' Perspectives of Interpersonal Contact during Patient Care. (May 2022) - De Luca, Enrico; Wilson, Marian; Shaw, Michele R.; Landis, Tullamora T.
The purpose of this study was to describe nurses' perceptions about the use of interpersonal touch in their clinical practice. A qualitative descriptive approach with content analysis method was used to identify common themes. Registered nurses (N = 22) participated in focus groups and individual interviews. Three themes emerged from the analysis: (a) touch and massage as a resource, (b) individualized boundaries, and (c) professional role conflict. While the approach to touch varied, stories about the positive impacts that touch can have on patient care were consistently evident throughout the data. Implications for practice include incorporating areas from the themes into the development of educational programs focusing on how to integrate touch into practice as a comforting resource, while keeping individual's preferences in mind.